+0  
 
0
99
4
avatar

Compute \(\large \sin10^\circ \sin30^\circ \sin50^\circ \sin70^\circ\)

 Jul 11, 2020

Best Answer 

 #2
avatar+8340 
+1

\(\quad\sin 10^\circ \sin 30^\circ \sin 50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin 50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin(60^\circ - 10^\circ)\sin(60^\circ + 10^\circ)\)

 

Now, use the identity: \(4\sin x \sin (60^\circ - x)\sin(60^\circ + x) = \sin 3x\) and substitute x = 10o.

 

\(\quad \sin10^\circ \sin30^\circ \sin50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin(60^\circ - 10^\circ) \sin(60^\circ + 10^\circ)\\ = \dfrac18 \left(4\sin 10^\circ \sin(60^\circ - 10^\circ) \sin(60^\circ + 10^\circ)\right)\\ = \dfrac18 \left(\sin(3\cdot 10^\circ)\right)\\ = \dfrac18 \sin 30^\circ\\ = \dfrac18 \cdot \dfrac12\\ = \dfrac1{16}\)

 Jul 11, 2020
 #1
avatar+10028 
+1

\(\large \sin10^\circ \cdot \sin30^\circ \cdot \sin50^\circ \cdot \sin70^\circ\color{blue}= 0.0625 \)

 

\(Hello\ Guest!\)  

 

\({\displaystyle {sin\ x=\frac {1}{2\mathrm {i} }}\left(\mathrm {e} ^{\mathrm {i} x}-\mathrm {e} ^{-\mathrm {i} x}\right)}\)

 

\(\large \sin\frac{\pi}{18} \cdot \sin\frac{3\pi}{18} \cdot \sin\frac{5\pi}{18} \cdot \sin\frac{7\pi}{18}\)

 \(={\displaystyle {\frac {1}{2\mathrm {i} }}\left(\mathrm {e} ^{\mathrm {i} \frac{\pi}{18}}-\mathrm {e} ^{-\mathrm {i} \frac{\pi}{18}}\right)}\times\)\({\displaystyle {\frac {1}{2\mathrm {i} }}\left(\mathrm {e} ^{\mathrm {i} \frac{3\pi}{18}}-\mathrm {e} ^{-\mathrm {i} \frac{3\pi}{18}}\right)}\)

              \(\times {\displaystyle {\frac {1}{2\mathrm {i} }}\left(\mathrm {e} ^{\mathrm {i} \frac{5\pi}{18}}-\mathrm {e} ^{-\mathrm {i} \frac{5\pi}{18}}\right)}\)\({\displaystyle {\times \frac {1}{2\mathrm {i} }}\left(\mathrm {e} ^{\mathrm {i} \frac{7\pi}{18}}-\mathrm {e} ^{-\mathrm {i} \frac{7\pi}{18}}\right)}\)

\(\large =0.0625\)

laugh  !

.
 Jul 11, 2020
edited by asinus  Jul 11, 2020
 #2
avatar+8340 
+1
Best Answer

\(\quad\sin 10^\circ \sin 30^\circ \sin 50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin 50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin(60^\circ - 10^\circ)\sin(60^\circ + 10^\circ)\)

 

Now, use the identity: \(4\sin x \sin (60^\circ - x)\sin(60^\circ + x) = \sin 3x\) and substitute x = 10o.

 

\(\quad \sin10^\circ \sin30^\circ \sin50^\circ \sin 70^\circ\\ = \dfrac12 \sin 10^\circ \sin(60^\circ - 10^\circ) \sin(60^\circ + 10^\circ)\\ = \dfrac18 \left(4\sin 10^\circ \sin(60^\circ - 10^\circ) \sin(60^\circ + 10^\circ)\right)\\ = \dfrac18 \left(\sin(3\cdot 10^\circ)\right)\\ = \dfrac18 \sin 30^\circ\\ = \dfrac18 \cdot \dfrac12\\ = \dfrac1{16}\)

MaxWong Jul 11, 2020
 #3
avatar+8340 
+1

Appendix: Why is \(4 \sin x \sin(60^\circ - x) \sin(60^\circ + x) = \sin 3x\\ \)?

 

Proof:

 

Using compound angle formula,

 

\(4\sin x\sin(60^\circ - x) \sin(60^\circ + x) = 4\sin x \left(\sin 60^\circ \cos x - \cos 60^\circ \sin x\right)\left(\sin 60^\circ \cos x + \cos 60^\circ \sin x\right)\)

 

Simplifying,

 

\(4\sin x\sin(60^\circ - x) \sin(60^\circ + x) = 4\sin x \left(\dfrac{\sqrt 3}2 \cos x - \dfrac12 \sin x\right)\left(\dfrac{\sqrt 3}2 \cos x + \dfrac12 \sin x\right) \)

\(4\sin x\sin(60^\circ - x) \sin(60^\circ + x) = \sin x \left(\sqrt 3 \cos x - \sin x\right)\left(\sqrt 3 \cos x + \sin x\right)\)

 

Now, by the identity \(a^2 - b^2 = (a - b)(a + b)\),

\(4\sin x\sin(60^\circ - x) \sin(60^\circ + x) = \sin x (3\cos^2 x - \sin^2 x)\)

 

Starting from the right hand side, expanding using triple angle formula,

(if you haven't learnt that yet, you can try expanding it with compound angle formula and double angle formula.)

\(\sin 3x = 3\sin x - 4\sin^3 x\)

 

Now, it suffices to show that \(\sin x (3\cos^2 x -\sin^2 x) = 3\sin x - 4\sin^3 x\)

 

To do so, we use the identity \(\cos^2 x = 1-\sin^2 x\).

 

\(\sin x (3\cos^2 x -\sin^2 x) = \sin x(3(1 - \sin^2 x) - \sin^2 x) = \sin x (3 - 3\sin^2 x - \sin^2 x) = \sin x (3 - 4\sin^2 x) = 3\sin x - 4\sin^3 x\)

 

Therefore, the original identity \(4 \sin x \sin(60^\circ - x) \sin(60^\circ + x) = \sin 3x\\ \) is true.

MaxWong  Jul 11, 2020
 #4
avatar+25541 
+1

Compute  
\(\large \sin(10^\circ) \sin(30^\circ) \sin(50^\circ) \sin(70^\circ)\)


Formula:
\(\begin{array}{|lrcll|} \hline (1) & \cos(x-y) &=& \cos(x)\cos(y)+\sin(x)\sin(y) \\ (2) & \cos(x+y) &=& \cos(x)\cos(y)-\sin(x)\sin(y)\\ \hline (1)-(2): & \mathbf{2\sin(x)\sin(y)} &=& \mathbf{\cos(x-y)-\cos(x+y)} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \sin(10^\circ) \sin(30^\circ) \sin(50^\circ) \sin(70^\circ) \quad | \quad \sin(30^\circ)=\dfrac{1}{2} \\ &=& \dfrac{1}{2}* \sin10(^\circ) \sin(70^\circ) \sin(50^\circ) \\ \hline \\ && \quad 2\sin(x)\sin(y)=\cos(x-y)-\cos(x+y) \\ && \quad 2\sin(10^\circ)\sin(70^\circ)=\cos(60^\circ)-\cos(80^\circ) \quad | \quad \cos(60^\circ)=\dfrac{1}{2} \\ &&\quad 2\sin(10^\circ)\sin(70^\circ)=\dfrac{1}{2}-\cos(80^\circ) \quad | \quad \cos(80^\circ)=\cos(90^\circ-10^\circ)=\sin(10^\circ) \\ &&\quad 2\sin(10^\circ)\sin(70^\circ)=\dfrac{1}{2}-\sin(10^\circ) \\ &&\quad \mathbf{\sin(10^\circ)\sin(70^\circ)=\dfrac{1}{4}-\dfrac{1}{2}*\sin(10^\circ)} \\ \\ \hline &=& \dfrac{1}{2}\left( \dfrac{1}{4}-\dfrac{1}{2}*\sin(10^\circ) \right) \sin(50^\circ) \\ &=& \dfrac{1}{8}\sin(50^\circ)-\dfrac{1}{4}*\sin(10^\circ)\sin(50^\circ) \\ \hline \\ && \quad 2\sin(x)\sin(y)=\cos(x-y)-\cos(x+y) \\ && \quad 2\sin(10^\circ)\sin(50^\circ)=\cos(40^\circ)-\cos(60^\circ) \quad | \quad \cos(60^\circ)=\dfrac{1}{2} \\ && \quad 2\sin(10^\circ)\sin(50^\circ)=\cos(40^\circ)-\dfrac{1}{2} \quad | \quad \cos(40^\circ)=\cos(90^\circ-50^\circ)=\sin(50^\circ) \\ &&\quad 2\sin(10^\circ)\sin(50^\circ)=\sin(50^\circ)-\dfrac{1}{2} \\ &&\quad \mathbf{\sin(10^\circ)\sin(50^\circ)=\dfrac{1}{2}*\sin(50^\circ)-\dfrac{1}{4} } \\ \\ \hline &=& \dfrac{1}{8}\sin(50^\circ)-\dfrac{1}{4}*\left(\dfrac{1}{2}\sin(50^\circ)-\dfrac{1}{4}\right) \\ &=& \dfrac{1}{8}\sin(50^\circ)-\dfrac{1}{8}\sin(50^\circ)+\dfrac{1}{16} \\ &=& \mathbf{\dfrac{1}{16}} \\ \hline \end{array} \)

 

laugh

 Jul 12, 2020
edited by heureka  Jul 13, 2020

21 Online Users

avatar